Different Types of Bully Experiences and Their Relationship with Attachment to Father and Moral Maturity - YILDIZ İNANICI, SİNEM (SPRINGER, 2021)
Bullying is a common misbehavior among some adolescent groups. It is a multifaceted phenomenon so it is important that researchers consider family related variables in addition to developmental ones. The aim of this study was to investigate whether moral maturity and attachment to father are associated with specific types of bullying experiences. Six hundred and forty eight adolescents (M = 15.86, SD = 0.94) participated in the study. Participants were 9th-11th grade students. The questionnaire included demographic information, The Revised Olweus Bully/Victim Questionnaire and Inventory of Parent and Peer Attachment (Father Form-Short). Descriptives, frequencies, Chi-square Tests, Kruskal-Wallis Test, Spearman correlation, and Multinomial Regression Analysis were executed. Students categorized by their bullying experiences as follows: 40.5% (n = 256) were neither bully nor victim; 13.3% (n = 84) were only bully; 20.3% (n = 128) only victim and 25.9% (n = 164) were both bully and victim. Neither bully nor victim group had the highest rate of not witnessing to a violent act in a lifetime. And this group had better scores for attachment to father and moral maturity than the other bully groups. Age, gender, moral maturity and witnessing a violent crime emerged as predictors for belonging to bully experience groups. Different variables must be considered as predictors for several bullying groups. Results imply that being female is a vulnerability to be a victim and prevention programs must support students' moral maturity. Also, screening the students for possible past traumatic experiences and providing psychological help to traumatized ones are other important implications.
Keywords: Bully; Predictor; Moral development; Attachment to father; Violent event; BULLY/VICTIM PROBLEMS; MIDDLE SCHOOL; VICTIMS; GENDER; ADOLESCENCE; AGGRESSION; PREVALENCE; PREDICTORS; EMOTIONS; BEHAVIOR